A repetição como recurso para construção coerente do texto: aplicação em produções textuais do ENEM - Nogueira, Joani Almeida dos Santos (2021)
This dissertation is part of the research line “Reading, Writing and Teaching of Portuguese Language”, of the Postgraduate Studies Program in Portuguese Language of the Pontifical Catholic University of São Paulo, and has, as its theme, the study of segment repetition. lexicals as a cohesive and argumentative resource in the textual production of the note mil essays of ENEM. We defined the following guiding research question as a starting point: What functions does the use of repetitions of lexical segments play in the writing of texts used to assess the linguistic knowledge of high school students? Therefore, we will work with the hypothesis that repetition is used as an argumentation construction strategy. The general objective of our investigation is to develop a study on the forms and functions of repetition of lexical segments in note mil essays of ENEM. Regarding the specific objectives, we intend to: I) Identify the types of repetitions that occur in ENEM newsrooms evaluated as grade one thousand; II) Analyze, in newsrooms note mil, the functions assumed by repetition in the construction of textual cohesion; III) Verify, in the most recurrent type of repetition, the argumentative role it assumes. From a methodological point of view, this research is descriptive, qualitative in approach and interpretive. The theoretical contribution that supports the study is constituted by studies of orality and writing, developed by the following authors: Bessa Neto (1991); Marcuschi (1992, 2010, 2015); Kato (1995); Fávero, Andrade and Aquino (2000); Silva, Denise (2001); Fávero (2002); Antunes (2005); Koch (2015, 2016); Koch and Elias (2018); and Everett (2019). The corpus is made up of fifteen grades of ENEM essays, between the years 2016 and 2018, extracted from the GI website. We analyzed the written productions in a procedural way, in which we verified: the position and characterization of the lexical repetition; the crossing of the formal features of repetition and its function in relation to the type of text; and the quantity of data obtained, with the aim of verifying whether the repetitions of lexical segments are a cohesive linguistic resource capable of continuing the topic in focus through argumentative strategies. The results of the analyzes led us to confirm our hypothesis, since, in all fifteen essays evaluated, strategic repetition occurred to advance the text